Relationship Marketing Dimensions on Customer satisfaction and Customer Loyalty: A Review - C.M. , Veena Kumari (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
Relationship marketing is frequently employed by firms to improve their dealings with customers. A key challenge for researchers is to identify and understand how different variables influence important relationship outcomes such as customer loyalty and customer satisfaction. This study aims at analyzing the existing dimensions and also in finding out those variables which are considered to be more effective in creating customer loyalty and customer satisfaction.